MOLECULAR CHARACTERIZATION OF THE 16SR II GROUP OF PHYTOPLASMA ASSOCIATED WITH FABA BEAN (Vicia faba L.) IN SAUDI ARABIA - M. A. AL-Saleh; M. A. Amer (Journal of Animal and Plant Sciences, 2014)
This study was conducted to detect for the first time the occurrence of phytoplasma in symptomatic faba bean plants in Saudi Arabia. Faba bean is one of the most widely grown protein-producing food legumes. Ten leaf and stem samples showing symptoms of phyllody and stunting were collected from plants grown in Agricultural Research Station field Riyadh region, Saudi Arabia during December, 2011. The temperature in this area ranged between 15-20ºC. Two representative faba bean symptomatic leaves out of the total samples collected from the field in the visited area tested positive for plant pathogenic phytoplasmas using P1/P7 primer pair in the first round of PCR analysis. Nested PCR was conducted using the R16F2n/R16R2 primer pair, which yielded fragment of approximately 1.2 kb.  No PCR products were obtained from the DNA extraction from asymptomatic plants. Phylogenetic analysis of the 16S rRNA gene of the obtained nucleotide sequence indicated that the two faba bean phytoplasmas isolates (faba bean phyllody and faba bean stunting) collected from Riyadh region of Saudi Arabia were more closely related to the phytoplasmas peanut witches’-broom group since its 16Sr RNA sequence showed a 97.2% to 99.3% identity with most members of this group. The nucleotide sequence for the Saudi Arabian isolates in this study were deposited in the GenBank with accession no. JQ861532 and JQ861533 respectively. The rest of the collected samples were assayed using cDNA probe for phytoplasma detection by dot and tissue blot hybridization. No hybridization was observed with DNA extracts from healthy plants.
Keywords: Faba bean; Phytoplasma; PCR; 16SrII group; sequence; cDNA probe